Implementasi Protokol MQTT Pada Monitoring Suhu Dan Ketersediaan Pakan Ikan Pada Akuarium - Moh. Saifud Daulah; Dahnial Syauqy; Rakhamadhany Primananda (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Fish feeding is generally still very dependent on human resources that are still manual. Also knowing the temperature in the aquarium water is also necessary for the maintenance of fish. However, there is still much indifference to the temperature and feeding of irregular fish. So we need a system of fish feeding automation and monitoring of temperature conditions in the water. In this system using DS18B20 temperature sensor to know the temperature in the aquarium and loadcell sensor is used to determine the availability of fish feed on the container. The loadcell sensor is used to determine the change of the weight of the container that holds the fish feed, so that information is forwarded to the application. Information obtained by hardware is sent to the application using MQTT protocol communication where data is sensed. The hardware acting as a publisher will send the data to the broker. Applications android acting subscriber will display data in the form of water temperature information, the availability of feed and fish feed scheduling based on information obtained from the hardware. Based on the results of the tests performed is the average percentage error error of 21.87%. Then for the average weight value of feed out for 5 seconds of 28.29 gr. Scheduling for open feed cover is done every 1 minute.